Developing Syllabus for Medical Academic Purposes for Indonesian Undergraduate Medical Students - Rinawati, Rinawati (LPPM Universitas Pekalongan, 2025)
English for Medical purposes is increasingly important in medical education to prepare students to actively participate in international scientific communication. However, medical students in Indonesia still face challenges in oral communication and academic writing, making them less than optimal in following global discourse. This study uses a Research and Development (R&D) approach in its second stage, namely planning for English for medical academic purposes syllabus. Document analysis was conducted on existing lecture materials, case scenarios in medical education, and international frameworks in scientific communication and the previous need analysis. The designed syllabus systematically integrates four language skills namely speaking, listening, reading, and writing, through learning activities such as Small Group Discussion (SGD) using the Seven Steps to Problem Solving (7-Jump Step) method, oral presentation training, article structure analysis, and medical text evaluation using the Introduction, Methods, Results, and Discussion/IMRAD, Setting, Population, Intervention, Condition, Endpoint (SPICED), and Consolidated Standards of Reporting Trials/CONSORT models. The EMAP syllabus provides a practical and contextual model for integrating language and content in medical education Keywords: English for Medical and Academic Purposes ; syllabus design, Research and Development